Addressing Shape and Extent of Weyl cones in TaAs by Landau level spectroscopy - Santos-Cottin, David; Wyzula, Jan; Florian Le Mardelé; Crassee, Iris; Martino, Edoardo; Eguchi, Gaku; Rukelj, Zoran; Novak, Mario; Orlita, Milan; Akrap, Ana (arXiv.org, 2021)
Tantalum arsenide, TaAs, is a prime example of a topological semimetal with two types of Weyl nodes, W1 and W2, whose bulk signatures have proven elusive. We apply Landau level spectroscopy to crystals with multiple facets and identify -- among other low-energy excitations between parabolic bands -- the response of a cone extending over a wide energy range. Comparison with density functional theory studies allows us to associate this conical band with nearly isotropic W2 nodes. In contrast, W1 cones, which are more anisotropic and less extended in energy, appear to be buried too deep beneath the Fermi level. They cannot be accessed directly. Instead, the excitations in their vicinity give rise to an optical response typical of a narrow-gap semiconductor rather than a Weyl semimetal.